Human T lymphotropic virus type I associated myelopathy with pulmonary and cutaneous lesions. Issue 3 (March 1993) - Kuwabara, H; Katanaka, J; Nagai, M; Uda, H; Hojo, W; Yamada, A; Miki, H; Takeuchi, H; Teranishi, K; Matsuda, K
Abstract : A necropsy case of human T lymphotropic virus I (HTLV-I) associated myelopathy (HAM) in a 64 year old man with serological and genetical confirmation of HTLV-I infection is reported. The spinal cord, lung, and skin were mainly affected. Severe degeneration had occurred in the spinal cord, not only in the lateral columns but also in the anterior and posterior columns. The degenerate lesions showed proliferation of capillaries, loss of myelin and axon, and perivascular and parenchymal infiltration with T lymphocytes and foamy macrophages in the white matter. T lymphocytes had infiltrated the lung and there was vascular proliferation in the peribronchus. OPD4 positive cells predominated in the lung. The patient also had erythrodermia where dense and bandlike HTLV-I infected lymphoid cell infiltration was observed, with mild atypia and epidermotropism. HTLV-I may cause multiorganic inflammatory disorders, although the definitive role of HTLV-I in the pathogenesis is still unknown.